Relationship of demoralization with anxiety, depression, and demographics of Chinese dialysis patients - Cai-Lan Zhuang; Juan-Lian Zheng; Lei Gao; Ying-Ling Huang; Wen-Jing Hu (Wolters Kluwer Medknow Publications, 2021)
Objective: The purpose of this study is to investigate the demoralization level of dialysis patients in China and analyze the influencing factors. Materials and Methods: A convenience sample of 278 dialysis patients from a tertiary hospital participated in a cross-sectional descriptive study using a structured questionnaire including assessments of demographic data, Demoralization Scale-II (DS-II), and Hospital Anxiety and Depression Scale. The main analysis consisted of descriptive statistics, correlation coefficients, and multiple linear regression. Results: The mean standard deviation DS-II score was 11.87 (7.72). Dialysis patients had a high level of demoralization. Findings from multiple linear regression indicated that demoralization was positively correlated with marital status (β = 0.141; P = 0.001), employment status (β = 0.113; P = 0.006), anxiety (β = 0.393; P < 0.001), and depression (β = 0.224; P < 0.001). These variables explained 57.1% of the variance in patient demoralization. Conclusions: Demoralization is common in dialysis patients and is associated with marital status, employment status, anxiety, and depression. Health-care providers might regularly assess demoralization in dialysis patients, and develop related interventions to improve the quality of life.